Ekonomi Qurani: Upaya Menjaga stabilitas ekonomi Di Tengah Ketidakpastian Global - Mimin Mintarsih; Abdillah (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2025)
Increasing global economic uncertainty, characterized by international market fluctuations, economic crises, and the effects of climate change, demands a search for a more stable and sustainable economic model. One attractive approach is Quranic economics, which is based on the teachings of the Qur'an and Islamic principles. This article explores how Quranic economics can contribute to maintaining economic stability amid global uncertainty. The research utilizes the content analysis method of relevant literature to identify the basic principles of Quranic economics and their applicability in the global context. The results show that the key principles of Quranic economics include social justice, prohibition of usury, transparency and honesty, and environmental responsibility. The implementation of these principles can be done through sharia-based financial systems, prudent risk management, sustainable economic development, microeconomic empowerment, and wealth redistribution. By applying these principles, economic stability and better welfare are expected. Despite the challenges, the potential benefits of a Quranic economy offer a significant alternative to global uncertainty.